Mapping and facies analysis of Paleocene–Mid-Eocene seismic sequences, offshore southern West Greenland - Dalhoff, Finn; Chalmers, James A; Gregersen, Ulrik; Nøhr-Hansen, Henrik; Audun Rasmussen, Jan; Sheldon, Emma (Marine and petroleum geology, 2003)
New interpretations are reported of the sedimentology and sequence stratigraphy of the Palaeogene sediments encountered by the boreholes Hellefisk-1, Ikermiut-1, Kangâmiut-1, Nukik-1 and Nukik-2 offshore southern West Greenland. These interpretations, together with new biostratigraphic and palaeoenvironmental interpretations, have been used to correlate the boreholes and to calibrate seismic sequences interpreted on a grid of reflection seismic data. The interpreted seismic sequences lie between major regional unconformities of Danian and mid-Eocene age. The new interpretations show that the area offshore southern West Greenland was subject to major uplift and erosion during the Danian when latest Cretaceous sediments were removed. Sedimentation restarted in the late Danian, coevally with major volcanism in central West Greenland and the start of sea-floor spreading in the Labrador Sea. Late Paleocene sediments were deposited in a predominantly extensional tectonic environment. The extensional stresses continued in most areas during the early Eocene, but in the northern and northwestern part of the basins, a transtensional system developed along the strike-slip faults that transferred sea-floor spreading movements between the Labrador Sea and Baffin Bay. Sediment input to the basins was predominantly from the north, possibly from a major river system flowing out of central Greenland. Lesser amounts of sediment came from the east, from the mainland of Greenland, and minor amounts from the west. The thickness of total sediment decreases substantially from north to south. The sediments were deposited in environments that ranged from fresh-water/marginal marine to upper bathyal. Proximal environments are probably generally sand-prone, but distal environments probably contain larger amounts of mud, some of which could contain a mature source rock for oil. Basin-floor fans, syn-tectonic wedges and turbidite channel complexes that could act as hydrocarbon reservoirs sealed by surrounding muds have been identified in many of the seismic sequences.